Bagi hasil sistem tellon di Madura perspektif ekonomi Islam - Ferdianto, Oktavian; Sakinah, Sakinah; Fahrurrozi, Fahrurrozi; Yakin, Ainol; Hidayati, Yulia Eva (AL-Muqayyad, 2024)
In the Madura region, collaboration between landowners and tenant farmers is commonly observed. One such collaboration occurs in tobacco farming. The Madurese community practices the tellon profit-sharing system in tobacco farming partnerships. This study aims to understand how the tellon profit-sharing system is implemented in the tobacco farming practices of the Madurese community. It also seeks to evaluate the alignment of the tellon system with Islamic economics principles. The study employs a qualitative descriptive method, utilizing literature reviews and direct interviews involving landowners and tenant farmers. These parties engage in collaborative efforts in tobacco farming and implement the tellon profit-sharing system. The findings reveal that cooperation within the Madurese community is driven by mutual dependency. The tellon profit-sharing system, rooted in mutual agreement between the parties, aligns with the principles of Islamic profit-sharing systems.